2021
DOI: 10.1108/imr-12-2020-0280
|View full text |Cite
|
Sign up to set email alerts
|

Cross-disciplinary issues in international marketing: a systematic literature review on international marketing and ethical issues

Abstract: PurposeThe purpose of this paper is to discuss the evolution of the cross-disciplinary area of ethics and international marketing and to highlight the current and future scope of research in this area.Design/methodology/approachThe authors conducted a systematic literature review (SLR) of research papers from reputed journals which publish articles in this cross-disciplinary subject area. This paper especially investigates the perception, issues, concepts and theories used in ethics and international marketing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…After 40+ years of country‐of‐origin research, important questions remain regarding ‘how, when, and why’ country image becomes an influencing factor for (anti‐)consumption decisions (Chatterjee et al, 2021; Insch et al, 2017). Overall, the findings of this study shed light on potential mechanisms that underlie (macro) country image influences on two major cognitive and affective determinants of consumer responses to foreign products: (micro) foreign product judgements and (macro) consumer animosity (Diamantopoulos et al, 2020; Kock et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After 40+ years of country‐of‐origin research, important questions remain regarding ‘how, when, and why’ country image becomes an influencing factor for (anti‐)consumption decisions (Chatterjee et al, 2021; Insch et al, 2017). Overall, the findings of this study shed light on potential mechanisms that underlie (macro) country image influences on two major cognitive and affective determinants of consumer responses to foreign products: (micro) foreign product judgements and (macro) consumer animosity (Diamantopoulos et al, 2020; Kock et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There is consensus that country cues affect people's consumption and anti‐consumption of foreign products (Ortega‐Egea & García‐de‐Frutos, 2021). However, country‐of‐origin effects have not been fully elucidated yet; important questions remain regarding ‘how, when, and why’ foreign country information becomes more influential (Chatterjee et al, 2021; Insch et al, 2017), particularly in relation to negative or controversial issues affecting consumer views of foreign countries and products. The latter is important in open Western economies, where emerging manufacturing countries and industries have been the subject of much public criticism regarding questionable policies and practices (Chatterjee et al, 2021; Dekhili et al, 2021; McNeill & Moore, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that by improving the absorptive capacity and dynamic capability, a firm can improve its operational performance [26,27]. Operational performance is referred to as the net outcome of a firm's overall processes and practices, including production cycle time, reliability, as well as inventory turnover, which involves measure of market share and satisfaction level of the customers [28][29][30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is theoretically and practically important to contrast the consequences of jay customers and abusive supervision on service workers burnout and customer orientation before and during the pandemic (Sheshadri, 2020; Rana et al , 2021). Determining if the negative impacts of workplace interpersonal stressors are exacerbated during COVID-19 can help to our understanding of workplace interpersonal stressors by positing the unprecedented pandemic as a boundary condition for such stressors from a theoretical perspective (Rana and Sheshadri, 2021; Sakka et al , 2021a). It also has ramifications for service companies attempting to address the pressures that FSEs face at work.…”
Section: Introductionmentioning
confidence: 99%